Evaluation of the effectiveness and efficiency of MASER and Bigram methods in retrieving Hadith documents / Mohd Yusof Mohd Zain - Mohd Zain, Mohd Yusof (2004)
Information can be in the form of text, image or sound. Current technology features allow Internet users to retrieve any documents that are available from online databases. The main issue in this information age is the efficiency and effectiveness of the retrieval system that can be used by the information provider. A good retrieval system should provide tools to perform searching accurately based on user requirement. This thesis concerns a Malay language documents retrieval system. In this study, MASER and Bigram method, Malay Hadith translated documents, query words and relevant judgments are used. Before the experiments can be done, the Hadith test collections must be built first. These collections are then conflated using Bigram method and hence known as Bigam-Hadith and Bigram-query. Besides, these collections are also conflated using both MASER and Bigram algorithms and hence known as Maser-Hadith and Maser-query. All experiments are using the best threshold value which is 1.0. This threshold value is the result of the experiment done before the start of this thesis project. However, using Maser-Hadith and Maserquery do not yield the best effectiveness results. However, these experiments can serves as a benchmark for future research in retrieving information in Malay language.